DEVELOPMENT AND IMPLEMENTATION OF A DISTANCE COURSE FOR PROSPECTIVE FOREIGN LANGUAGE TEACHERS - Plotnikov, Yevhen O. (Educological discourse, 2015)
The article focuses on the architecture and key structural components of a foreign language distance course using as an example the course developed in Nizhyn State Gogol University to train high school graduates for external independent testing in English. The peculiarities and benefits of a modular structure of a distance learning environment are specified. The hierarchy and interoperability of the main levels of learning objects in a foreign language distance course are defined and analyzed. Special attention is paid to some possible ways of interactivity and feedback realization.